Requirement and challenge of holographic-type communication to the future network - Xiaozhi YUAN; Li PENG; Linfeng ZHANG (Dianxin kexue)
With the acceleration of 5G global commercial deployment process,various emerging immersive network applications represented by holographic communication have put forward significant requirements and tests on the structure and capability of the existing network architecture.The wide application of holographic communication services in many fields was introduced,and the current situation was analyzed that 5G network can not meet the rapid development needs of holographic immersion applications.The performance requirements of holographic communication applications in bandwidth,delay,computing power,synchronization,quality of service,reliability,security and other aspects of the future network performance were analyzed.The application scenarios and key technologies of holographic communication were summarized.Through the investigation and analysis of the possible evolution routes of the future network,the direction of the future network evolution and development was pointed out.